Shadow Stadia and the Circular Economy - Barry, Taryn; Mason, Daniel S.; Heise, Lisi (Frontiers in Sports and Active Living, 2022)
Most attention on stadium or arena-anchored development projects is placed on the scope and construction of the new sports facility, while less emphasis is on the facility left behind, which we describe as shadow stadia. Some shadow stadia are repurposed for mixed use development, others are demolished but have delayed redevelopment plans, while some remain abandoned and empty for years after the professional sports team or event is no longer present in the facility. The environmental impacts of shadow stadia are not fully understood, as limited research exists on how the immediate neighborhood anchored by pre-existing venues cope in the shadows of these new development plans and the loss of a sport venue and its events. Green strategies such as the circular economy may extend the lifecycle of existing sport faciltiies. To contribute to this discussion further, this perspective article will first discuss current advances in the academic literature on the circular economy. Second, it will present a comprehensive categorization of shadow stadia globally and future opportunities on integrating circularity into best practices. By doing so, this perspective article highlights several areas of future investigation that should be considered and planned for when major league sports teams and city leaders move their team and build new facilities.